2016
DOI: 10.1002/adma.201603601
|View full text |Cite
|
Sign up to set email alerts
|

Probing Bilayer Grain Boundaries in Large‐Area Graphene with Tip‐Enhanced Raman Spectroscopy

Abstract: The bilayer grain boundaries (GBs) in chemical-vapor-deposition-grown large-area graphene are identified using multispectral tip-enhanced Raman imaging with 18 nm spatial resolution. The misorientation angle of the bilayer GBs is determined from a quantitative analysis of the phonon-scattering properties associated with the modified electronic structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 32 publications
4
39
0
Order By: Relevance
“…Confocal Raman spectroscopy gives spatially resolved information about the vibrational spectrum, so-called Raman images. A state of the art Raman imaging system can achieve a spatial resolution of B300 nm if we do not use some special techniques, such as near-field Raman technique, tip enhanced Raman scattering (TERS), 311 or microspheres (or lens). With the development of high-performance charge-coupled devices (CCDs) and also the optimization of optical items, the integration time required for obtaining a smooth Raman spectrum can be as short as milliseconds, which greatly minimizes the time to acquire Raman imaging.…”
Section: Raman Images Of Graphene Flakesmentioning
confidence: 99%
“…Confocal Raman spectroscopy gives spatially resolved information about the vibrational spectrum, so-called Raman images. A state of the art Raman imaging system can achieve a spatial resolution of B300 nm if we do not use some special techniques, such as near-field Raman technique, tip enhanced Raman scattering (TERS), 311 or microspheres (or lens). With the development of high-performance charge-coupled devices (CCDs) and also the optimization of optical items, the integration time required for obtaining a smooth Raman spectrum can be as short as milliseconds, which greatly minimizes the time to acquire Raman imaging.…”
Section: Raman Images Of Graphene Flakesmentioning
confidence: 99%
“…Tip-enhanced Raman spectroscopy (TERS) can simultaneously provide the high spatial resolution and chemical sensitivity needed for materials and device characterisation at the nanoscale through the highly confined enhanced electromagnetic field generated within a plasmonic nano-cavity. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] It has recently been demonstrated that TERS systems based on a scanning tunnelling microscope (STM) can obtain impressive images and information with subnanometre resolution, [10][11][12] but these systems are restricted to special extreme environments (e.g. ultra-high vacuum and low temperature) that are not suitable to study the asfabricated electrical and mechanical properties of devices.…”
Section: Introductionmentioning
confidence: 99%
“…Raman intensity changes in CVD-grown monolayer graphene are mainly related to defects, (folded) wrinkles, and overlaps of the graphene layers. Wrinkles are usually formed during the post-growth cooling of graphene on a Cu substrate owing to the difference in thermal expansion coefficients between graphene and Cu 10 , 26 . Polycrystalline graphene consists of single-crystal domains with different crystallographic orientations.…”
Section: Resultsmentioning
confidence: 99%
“…Polycrystalline graphene consists of single-crystal domains with different crystallographic orientations. The individual domains are merged together with the formation of defects, wrinkles, and/or overlapped structures at the domain boundaries 10 , 26 , 27 . Moreover, defective or atomically smooth connections can be formed at the domain boundaries with flat interfaces 27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation